Studi Eksperimental Penggantian Sebagian Semen dengan Kombinasi Serbuk Kapur dan Serbuk Bata Merah untuk Beton Ramah Lingkungan - Priska Gardeni Nahak; Melchior Bria; Anastasia Henderina Muda; Jusuf Wilson Meynerd Rafael; Praty Dewi (Politeknik Negeri Jakarta, 2026)
This study aimed to evaluate the effect of partially replacing cement with a combination of lime and red brick powders on the compressive strength of eco-friendly concrete. The background of this study is based on the high carbon emissions from Portland cement production, necessitating more sustainable local material alternatives. Lime powder serves as a filler that enhances density and early hydration, whereas red brick powder has pozzolanic potential owing to its silica and alumina content. Concrete cylinder test specimens were created using a combination of 80% lime powder and 20% red brick powder, with variations in cement replacement of 0%, 5%, 15%, and 25%. The tests included a slump test for workability and compressive strength tests at 7 and 28 d. The test results showed that the control concrete (0% substitution) had an average compressive strength of 12,74 MPa, whereas the 5% substitution yielded 9,03 MPa, 15% substitution reached 9,43 MPa, and 25% substitution decreased to 7,46 MPa. Thus, 15% substitution can be considered a compromise between strength and sustainability, although none of the variations reached the target of 20 MPa. Further research is recommended to refine the optimal substitution ratio and explore long-term performance characteristics.